Corruption and Illegality in Asian Investment Arbitration (Springer Nature, 2024)
This open access book explores Asian approaches towards investment arbitration—a transnational procedure to resolve disputes between a foreign investor and a host state—setting it in the wider political economy and within domestic law contexts. It considers the extent to which significant states in Asia are, or could become, “rule makers” rather than “rule takers” regarding corruption and serious illegality in investor-state arbitration. Corruption and illegality in international investment are widely condemned in any society, but there remains a lack of consensus on the consequences, especially in investment arbitration. A core issue addressed is whether a foreign investor violating a host state’s law should be awarded protection of its investment, as per its contract with the host state and/or the applicable investment or trade agreement between the home state and the host state. Some suggest such protection would be unnecessary as the investor committed a crime in the host state, while others attempt to establish an equilibrium between the investor and the host state. Others claim to protect investment, invoking the sanctity of promises made. The book starts with a deep dive into economic and legal issues in corruption and investment arbitration and then explores the situation and issues in major countries in the region in detail. It is a useful reference point for lawyers, economists, investors, and government officials who are seeking comprehensive and up-to-date information on anti-bribery rules in Asian investment treaties. It is of particular interest to students and researchers in economics, finance, and law, who are undertaking new research relating to the multifaceted impacts of corruption. ; This open access book explores Asian approaches towards investment arbitration — a transnational procedure to resolve disputes between a foreign investor and a host state — setting it in the wider political economy and within domestic law contexts. It considers the extent to which significant states in Asia are, or could become, “rule makers” rather than “rule takers” regarding corruption and serious illegality in investor-state arbitration. Corruption and illegality in international investment are widely condemned in any society, but there remains a lack of consensus on the consequences, especially in investment arbitration. A core issue addressed is whether a foreign investor violating a host state’s law should be awarded protection of its investment, as per its contract with the host state and/or the applicable investment or trade agreement between the home state and the host state. Some suggest such protection would be unnecessary as the investor committed a crime in the host state, while others attempt to establish an equilibrium between the investor and the host state. Others claim to protect investment, invoking the sanctity of promises made. The book starts with a deep dive into economic and legal issues in corruption and investment arbitration and then explores the situation and issues in major countries in the region in detail. It is a useful reference point for lawyers, economists, investors and government officials who are seeking comprehensive and up-to-date information on anti-bribery rules in Asian investment treaties. It is of particular interest to students and researchers in economics, finance and law, who are undertaking new research relating to the multifaceted impacts of corruption.